2018
DOI: 10.1103/physrevb.98.104306
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of spin-phonon coupling in CrSiTe3

Abstract: We present the Raman scattering results on layered semiconducting ferromagnetic compound CrSiTe3. Four Raman active modes, predicted by symmetry, have been observed and assigned. The experimental results are supported by DFT calculations. The self-energies of the A 3 g and the E 3 g symmetry modes exhibit unconventional temperature evolution around 180 K. In addition, the doubly degenerate E 3 g mode shows clear change of asymmetry in the same temperature region. The observed behaviour is consistent with the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
5
32
0
Order By: Relevance
“…Raman spectroscopy data were gathered to confirm the quality of the CGT films. Unlike the Raman spectra reported previously for CGT FETs, which were exposed to air, the Raman spectra of our CGT/Ta Hall bar devices (with 50 nm CGT) show sharp peaks at approximately 112 and 138 cm –1 (see Figure b), consistent with previously reported Raman spectra on single‐crystal CGT . Figure S2a , Supporting Information, shows a similar Raman spectrum for a device from a thinner CGT flake, indicating that our process flow does ensure high‐quality devices even when thinner CGT flakes are employed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Raman spectroscopy data were gathered to confirm the quality of the CGT films. Unlike the Raman spectra reported previously for CGT FETs, which were exposed to air, the Raman spectra of our CGT/Ta Hall bar devices (with 50 nm CGT) show sharp peaks at approximately 112 and 138 cm –1 (see Figure b), consistent with previously reported Raman spectra on single‐crystal CGT . Figure S2a , Supporting Information, shows a similar Raman spectrum for a device from a thinner CGT flake, indicating that our process flow does ensure high‐quality devices even when thinner CGT flakes are employed.…”
supporting
confidence: 88%
“…Unlike the Raman spectra reported previously for CGT FETs, which were exposed to air, [12] the Raman spectra of our Figure 2b), consistent with previously reported Raman spectra on single-crystal CGT. [13,14] Figure S2a , Supporting Information, shows a similar Raman spectrum for a device from a thinner CGT flake, indicating that our process flow does ensure high-quality devices even when thinner CGT flakes are employed. The surface roughness of the fabricated devices is in the sub-nanometer range even after the Ta deposition, further highlighting the process control achieved (see Figure S2b, Supporting Information).…”
Section: Doi: 101002/adma201906021mentioning
confidence: 87%
“…2(a). Having in mind small instrumental broadening, the analysis of the line-shape was preformed by using Fano function alone 20,21 :…”
Section: Resultsmentioning
confidence: 99%
“…Raman scattering studies of CrSiTe 3 reveal strong spin–lattice coupling in the paramagnetic phase [ 15,21 ] as a consequence of a short‐range magnetic order in this compound. In addition to renormalization of energies and linewidths of observed Raman active modes, coupling of doubly degenerate E g mode with magnetic continuum was found.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to renormalization of energies and linewidths of observed Raman active modes, coupling of doubly degenerate E g mode with magnetic continuum was found. [ 21 ] The coupling results in an asymmetric phonon line shape up to 180 K. Besides the splitting of two low‐energy E g modes in the magnetic phase of CrGeTe 3 and unconventional behaviour of phonon properties around transition temperature, experimental results indicate spin–phonon coupling effect with magnetic quasi‐elastic scattering. [ 22 ] Pressure‐dependent Raman scattering study of CrGeTe 3 showed a decrease in bond length, the deviation of Cr–Te–Cr angle, and reduction of phase transition temperature.…”
Section: Introductionmentioning
confidence: 99%